Distribution and Morphometric Characteristics of Domesticated Rabbit Breeds in North Rift and Western Regions, Kenya - Sergon, P. C.; Wanga, J. O.; Rachuonyo, H.; Chemoiwa, E. J. (Africa Environmental Review Journal, 2022)
Rabbits (Otyctolagus cuniculus) occur throughout the world with their breeds distinctively identified phenotypically by coat color, body size and shape. The common rabbit breeds in Kenya are New Zealand White, Californian White, Flemish Giant, French Ear Lop, Chinchilla, Angora, Kenya White and their crosses. The present study was designed to assess morphometric characteristics of rabbit breeds in North and Western regions of Kenya. The combination of information derived from the study was intended to provide important baseline data for future breed conservation and production improvement in Kenya. Onsite study was conducted at University of Eldoret (UoE) Farm – Rabbitry Section. Rabbit breeds from farmers in the regions were obtained through snow balling technique. In order to investigate patterns of morphometric variation within and among the breeds, the study collected individual does and bucks from each county in the region and transported to University of Eldoret to be taken care of prior to weighing and taking linear body measurements Breeds were kept in standardized housing, feeding and health management were provided. Morphometric characterization was made according to Khalil (2010). Data collected were subjected to analysis using SPSS Version 21. The two regions had same breeds of rabbits (χ2=9.422, df=7, p=0.2240). For the counties within the regions in which the breeds were collected, New Zealand White was distributed in all counties with largest percentage in Baringo County (92.86%). Significant difference was between counties in the regions in which breed were collected (χ2=77.1940, df=49, p=0.0060). Majority of characteristics did not differ between male and female rabbits. As per sex, only female Agouti rabbits had larger ear length than males (t = 2.3378 P-value = 0.0393). New Zealand White females weighed more than males (t = 2.4226, p= 0.0194). Chinchilla rabbit breed had higher significant body length (51.00±4.15; F=2.49, p=0.0356). In terms of males’ weight, Palmino followed by Silver Fox had the highest weight (2.55±0.12; 2.49±0.57, respectively). For females, Chinchilla had the highest weight (3.31±0.48) than Rex (1.49±0.44) and Agouti (1.93±0.57). In conclusion, only weight differed in both males and females for all breeds. Only female Agouti rabbits had larger ear length than males. This research work recommends more studies be conducted on morphometric characterization of the indigenous rabbit at pre-determined ages including genetic, molecular, and immunological characterization and genetic parameter estimation. It is also recommended that breeding programs be carried out to improve the production performance of local rabbit.